Gestures - Flusser, Vilem, 1920-1991 (Book collections on Project MUSE., 2014)
'Gestures' is a collection of essays that proposes a daring and ambitious new conception of human behaviour. Defining gesture as 'a movement of the body or of a tool attached to the body for which there is no satisfactory causal explanation', Flusser moves around the topic from different points of view, angles and distances. Holding firmly to basic phenomenological principles - that consciousness is always consciousness of something, that we know others by reference to ourselves, he claims that we constantly 'read' states of mind, i.e. thoughts, intentions, emotions, from gestures.